You owe me - Ulrike Malmendier; Klaus M. Schmidt (Center for Economic Studies and ifo Institute (CESifo), 2012)
In many cultures and industries gifts are given in order to influence the recipient, often at the expense of a third party. Examples include business gifts of firms and lobbyists. In a series of experiments, we show that, even without incentive or informational effects, small gifts strongly influence the recipient's behavior in favor of the gift giver, in particular when a third party bears the cost. Subjects are well aware that the gift is given to influence their behavior but reciprocate nevertheless. Withholding the gift triggers a strong negative response. These findings are inconsistent with the most prominent models of social preferences. We propose an extension of existing theories to capture the observed behavior by endogenizing the reference group to whom social preferences are applied. We also show that disclosure and size limits are not effective in reducing the effect of gifts, consistent with our model. Financial incentives ameliorate the effect of the gift but backfire when available but not provided.
Keywords: C91; D73; I11; 330; gift exchange; externalities; lobbyism; corruption; reciprocity; social preferences